Bridging clinic: The initial medical management of patients with newly diagnosed pancreatic cancer. Issue 3 (9th October 2018) - Sreedharan, Loveena; Kumar, Bhaskar; Jewell, Anna; Banim, Paul; Koulouris, Andreas; Hart, Andrew R
Abstract : Pancreatic cancer is the 11th most common cancer in the UK and has the worst prognosis of any tumour with minimal improvements in survival over recent decades. As most patients are either ineligible for surgery or may decline chemotherapy, the emphasis is on control of symptoms and management of complications such as poor nutritional status. The time period between informing the patient of their diagnosis and commencing cancer treatments presents a valuable opportunity to proactively identify and treat symptoms to optimise patients' overall well-being. The 'bridging clinic', delivered by a range of healthcare professionals from gastroenterologists to nurse practitioners, can provide this interface where patients are first informed of their diagnosis and second supportive therapies offered. In this article, we provide a structure for instituting such supportive therapies at the bridging clinic. The components of the clinic are summarised using the mnemonic INDASH (Information/Nutrition/Diabetes and Depression/Analgesia/Stenting/Hereditary) and each is discussed in detail below.